A kind of polyacrylonitrile-based carbon fiber and preparation method thereof
By employing continuous polymerization, dry-spray wet molding, and multi-stage pre-oxidation carbonization processes, combined with electrolytic oxidation and ultrasonic-assisted surface treatment, the problem of insufficient strength and modulus of polyacrylonitrile-based carbon fibers was solved, and high-performance carbon fibers were prepared for use in composite materials.
Patent Information
- Application Number
- CN202211611067.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-14
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-12-14
AI Technical Summary
Existing polyacrylonitrile-based carbon fibers cannot simultaneously possess high strength and high modulus, making them unsuitable for structural applications with stringent requirements for reinforcement, weight reduction, and deformation control.
The polymerization solution is prepared by continuous polymerization process, and the fiber structure and properties are optimized by dry spray wet molding, multi-stage pre-oxidation and carbonization process, combined with electrolytic oxidation surface treatment. Ultrasonic-assisted surface treatment and special sizing agent system are used to improve the strength and modulus of the fiber.
Carbon fiber products with both high strength and high modulus were prepared, which are suitable for multiple technical fields and composite material molding processes, thus improving the overall performance and wide applicability of the fiber.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon fibers, and in particular to a polyacrylonitrile-based carbon fiber and a preparation method thereof. Background Art
[0002] Polyacrylonitrile-based carbon fiber began in the 1960s and industrialization began in the 1970s. After half a century of development, carbon fiber has achieved "standardization, serialization, generalization and practicality". In recent years, with the needs of applications and technological progress, higher-performance carbon fiber varieties have been continuously introduced, such as T1100 and M40X grade carbon fiber.
[0003] The launch of new generation carbon fiber such as T1100 and M40X carbon fiber reflects the development trend of carbon fiber materials from single advantage to balanced improvement of comprehensive performance. The strength of T1100 carbon fiber reaches 7000MPa and the modulus is also increased to 324GPa. Compared with the previous T800 and T1000 high-strength medium-modulus products, not only the strength is greatly improved, but also the modulus is improved. The strength of M40X carbon fiber is 5700MPa and the modulus is 377GPa, which has both the strength of T800 carbon fiber and the modulus of M40J carbon fiber.
[0004] The new generation of carbon fiber has ultra-high strength and relatively high modulus. It has great potential application value and extraordinary significance in strengthening structural parts with stringent requirements for weight reduction and extremely high requirements for deformation control. It has broad market prospects and is an ideal reinforcement for the next generation of advanced composite materials in the future.
[0005] Polyacrylonitrile-based carbon fibers have always had the defect of not being able to have both strength and modulus. Although there has been some progress in recent years, the systematic preparation of a new generation of carbon fiber products that have both strength and modulus is still a technical problem that we urgently need to solve.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a polyacrylonitrile-based carbon fiber and a preparation method thereof, aiming to prepare a new generation of carbon fiber products with both high strength and high modulus.
[0008] The present invention is achieved in that:
[0009] In a first aspect, the present invention provides a method for preparing polyacrylonitrile-based carbon fiber, comprising:
[0010] A continuous polymerization reaction is carried out with acrylonitrile as the main monomer to obtain a polymerization stock solution, and the polymerization stock solution is subjected to demonstration and degassing to obtain a homogeneous polymerization solution;
[0011] The homogeneous polymer solution is spun by a dry-wet-jet molding process to obtain spun fibers, and the spun fibers are sequentially washed, hot-water drawn, dried, steam drawn and oiled to obtain fiber precursors;
[0012] The fiber precursor is sequentially pretreated, preoxidized, and carbonized in multiple stages to obtain carbonized fiber;
[0013] The carbonized fiber is subjected to surface treatment, water washing, sizing and drying in sequence. The surface treatment is carried out by an electrolytic oxidation method.
[0014] In an optional embodiment, the preparation process of the polymerization stock solution includes: mixing and dissolving the first monomer and the second monomer, performing a polymerization reaction in the presence of an initiator, controlling the polymerization system temperature to 60-80° C., and the total polymerization time to 600-1300 min;
[0015] The first monomer is acrylonitrile, and the second monomer is selected from at least one of itaconic acid, sodium methacrylic acid sulfonate, sodium methacrylic acid benzene sulfonate, vinyl acetate, methyl methacrylate, methyl acrylate, acrylamide, isopropanol, dithioester and n-octyl mercaptan;
[0016] Preferably, the mass ratio of the amount of the first monomer to the total amount of monomers is 95-99:100;
[0017] Preferably, the initiator is selected from at least one of initiators containing nitrogen-nitrogen double bonds such as azobisisobutyronitrile and azobisisoheptylnitrile, and the solvent used for dissolution is selected from one of dimethyl sulfoxide, dimethylformamide, dimethylacetamide, and zinc dichloride;
[0018] Preferably, the polymerization adopts a three-reactor linkage continuous polymerization process, and the size of the polymerization reactor is 10 to 25 m 3 10~25m 3 and 5~15m 3 , control the total polymerization time of the three reactors to be 600–1300 min;
[0019] Preferably, the polymerization stock solution meets the following requirements: the solid content of the polymerization solution is 20-23wt%, the rotational viscosity is 100000-150000 cP, the weight average molecular weight is 250,000-300,000, the number average molecular weight is 100,000-130,000, the molecular weight distribution is 1.9-2.8, and the intrinsic viscosity is 2.1-2.5 dL / g.
[0020] In an optional embodiment, the process of removing monomers and degassing the polymer stock solution is to contact the polymer stock solution with the solvent in countercurrent, and the monomer content in the polymer solution after the removal of monomers is controlled to be 0-100 ppm;
[0021] Preferably, the tops of the single-removing tower and the degassing tower are evacuated to control the pressure inside the single-removing tower and the degassing tower to be 0-2 KPa.
[0022] In an optional embodiment, the process for preparing the spun fiber includes: ejecting a homogeneous polymer solution from a combined spinneret, passing through an air section and then through a multi-stage coagulation bath;
[0023] Preferably, the temperature of the homogeneous polymer solution for spinning is 50-60°C, the homogeneous polymer solution is extruded and filtered, and then sprayed out from the spinning plate, the height of the air section is 2-6mm, and the air layer draft ratio is 2.5-4.0;
[0024] Preferably, the pore size of the spinneret is controlled to be 0.06-0.09 mm, the pore spacing is 0.3-0.5 mm, the spinneret hole aspect ratio is 2-3, and the shape of the spinneret is spherical or flat;
[0025] Preferably, the multi-stage coagulation bath comprises at least a first coagulation bath and a second coagulation bath, each stage of the coagulation bath is a mixed solution formed by an organic solvent and water, the water content gradually increases from the first coagulation bath to the last stage of the coagulation bath, the organic solvent is the same as the solvent used in the polymerization stage, and each stage of the coagulation bath uses an alkali solution to adjust the pH value to 8-10;
[0026] More preferably, the mass fraction of the organic solvent in the first coagulation bath is 60-78%, the temperature is 40-60°C, and the draw ratio is 1.0-2.0; the mass fraction of the organic solvent in the second coagulation bath is 15-45%, the temperature is 50-70°C, and the draw ratio is 1.0-2.0.
[0027] In an optional embodiment, the spun fiber is washed with water for multiple stages, then hot water stretched at 80-95° C., dried, steam stretched at 130-160° C., and then oiled and heat-set to obtain fiber precursors; the fiber precursors are controlled to meet the following requirements:
[0028] The original single fiber fineness is 0.70-0.90dtex, the single fiber strength is 8.0-10.0cN / dtex, the single fiber modulus is 95-135cN / dtex, and the bulk density is 1.18-1.19g / cm 3 ;
[0029] Preferably, the hot water drawing is to control the drawing ratio to be 2.0-4.0, and the steam drawing is to operate with saturated steam, control the steam force to be 3.0-8.0 bar, and the steam drawing ratio to be 2.0-5.0;
[0030] Preferably, the multi-stage washing is carried out in 5-10 stages, each stage of washing corresponds to a washing tank and two sets of traction rollers, so that the fiber contacts the water flow in reverse direction, and the washing temperature is controlled to be 50-85°C;
[0031] Preferably, the drying after hot water drawing is carried out by using saturated steam, the steam pressure of the saturated steam is controlled to be 1.5-10 bar, a stepped pressure gradient design is adopted, and the number of drying rollers is 15-30.
[0032] In an optional embodiment, the oiling solution used in the oiling process includes, by weight, 60-75 parts of water, 15-20 parts of silicone oil, 5-10 parts of emulsifier, 1-5 parts of penetrant and 1-5 parts of antistatic agent; the overall oiling rate is controlled to be 1.0-2.5wt%;
[0033] Preferably, the oil is selected from at least one of dimethyl silicone oil and amino silicone oil;
[0034] The emulsifier is a nonionic surfactant, and more preferably, the emulsifier is selected from at least one of isomeric alcohol polyoxyethylene ether and fatty acid polyoxyethylene ether;
[0035] The penetrant is selected from at least one of alkyl sulfonates, quaternary ammonium salts and aliphatic ethers;
[0036] The antistatic agent is at least one of anionic, cationic and nonionic;
[0037] The anionic type is selected from at least one of alkyl sulfonates, carboxylates and phosphates;
[0038] The cationic type is selected from at least one of quaternary ammonium salts;
[0039] The nonionic type is selected from at least one of alkanolamides, polyethylene glycol stearate, polyols and polyglycerol stearate.
[0040] In an optional embodiment, the fiber precursor is pretreated first, and then pre-oxidized and multi-stage carbonized in sequence. The pre-oxidation is divided into 4-6 oxidation zones for treatment. The starting temperature of the oxidation zone is controlled to be 180-220°C, the ending temperature is controlled to be 245-270°C, the draft ratio of each temperature zone is 0.9-1.3, and the pre-oxidized yarn density is controlled to be 1.33-1.36g / cm 3 ;
[0041] Multi-stage carbonization is to carry out low-temperature carbonization, high-temperature carbonization and ultra-high-temperature carbonization in sequence. The starting temperature of low-temperature carbonization is 350℃-420℃, the ending temperature is 700℃-850℃, and the drawing ratio is 1.0-1.15; the starting temperature of high-temperature carbonization is 900℃-1200℃, the ending temperature is 1350℃-1450℃, and the drawing ratio is 0.95-1.0; ultra-high-temperature carbonization is to control the carbonization temperature to 1600℃-2300℃, and the drawing ratio is 1.0-1.1;
[0042] Preferably, the pretreatment is to immerse the fiber precursor in a pretreatment solution for 10-15 seconds, and the pretreatment solution comprises 96-99 parts of water, 1-2 parts of oil, 0.01-0.2 parts of modifier and 0.01-0.2 parts of pre-oxidation accelerator by weight.
[0043] Wherein, the oil agent is a modified polysiloxane, preferably, the oil agent is selected from at least one of amino-modified polysiloxane, polyether-modified polysiloxane and epoxy-modified polysiloxane;
[0044] The modifier is selected from at least one of boric acid, metaboric acid, tetraboric acid and boric acid esters;
[0045] The pre-oxidation accelerator is a peroxide, and the peroxide is selected from at least one of cumene hydroperoxide and di-tert-butyl peroxide;
[0046] More preferably, the pretreatment solution further comprises 0.5-1 part of an emulsifier, and the emulsifier is selected from at least one of nonylphenol polyoxyethylene ether and fatty alcohol polyoxyethylene ether.
[0047] In an optional embodiment, the carbonized fiber is surface treated by electrolytic oxidation, and the current density is controlled to be 0.5-1.5A / m 2 , the treatment time is 50-90s, the electrolyte temperature is 20-35°C, and the electrolyte is selected from at least one of ammonium bicarbonate solution, sodium bicarbonate solution and ammonium nitrate solution;
[0048] Preferably, the concentration of the electrolyte is 3-6wt%;
[0049] Preferably, an ultrasonic generator is installed on the surface treatment tank to irradiate the carbonized fiber with ultrasound, and the ultrasonic frequency is controlled to be 60-120kHz and the ultrasonic intensity is 4-8W / cm 2 .
[0050] In an optional embodiment, during the sizing process, the sizing amount of the sizing agent is controlled to be 1-2wt%, and the sizing agent includes 20-40 parts of epoxy resin, 20-40 parts of polyester resin, 10-20 parts of emulsifier and 1-5 parts of sizing agent by mass fraction;
[0051] Preferably, the emulsifier is selected from at least one of fatty acids and fatty alcohol polyoxyethylene ethers;
[0052] Preferably, the sizing agent is selected from at least one of polyurethane and polyamide;
[0053] Preferably, drying is performed after sizing, and the drying temperature is controlled to be 150-190°C.
[0054] In a second aspect, the present invention provides a polyacrylonitrile-based carbon fiber prepared by the preparation method of any one of the aforementioned embodiments.
[0055] The present invention has the following beneficial effects: the present invention uses acrylonitrile as the main monomer to continuously polymerize and prepare a polymerization stock solution, and the continuous polymerization has the characteristics of long-term stability and the like, and is more suitable for large-scale mass production of high-performance carbon fibers. The polymerization solution prepared by the formula and process system of the present invention has the characteristics of high molecular weight and narrow distribution, which is conducive to the formation of the designed precursor structure, and the regulation of the final carbon fiber structure has a positive effect on improving the strength and modulus of the carbon fiber. After stripping and degassing, a homogeneous polymerization solution is obtained, and the homogeneous polymerization solution is spun by a dry-jet wet molding process, and fiber precursors are obtained by sequentially undergoing process steps such as water washing, hot water drawing, drying, steam drawing and oiling. The precursor obtained by the dry-jet wet molding process has a smooth surface and few defects, and is the basis of high-strength carbon fibers. The method system involved in the present invention can obtain precursors with high fineness, high orientation and low defects, and form special polyacrylonitrile precursors for carbon fibers with strength, modulus characteristics and structural characteristics required by the final design. Subsequently, the precursor is sequentially pretreated, pre-oxidized, and multi-stage carbonized to obtain carbonized fibers; the carbonized fibers are sequentially surface treated, washed, sized, and dried to obtain carbon fiber products. The unique pre-oxidation pretreatment process system of the present invention can effectively improve the efficiency of the fiber in the pre-oxidation process, promote cyclization / oxidation / dehydrogenation reactions, avoid the generation of skin-core structures, and obtain homogeneous pre-oxidized fibers. The high-draw ratio carbonization process adopted by the present invention can effectively improve the orientation and crystallinity of the fiber, eliminate defects such as pores, and achieve the simultaneous acquisition of high strength and high modulus.
[0056] In addition, in a preferred embodiment, the present invention effectively improves the surface treatment effect of high modulus fibers by applying ultrasonic-assisted surface treatment, achieves deep and homogeneous surface treatment, and the supporting special sizing agent system further enhances the surface properties of the fibers, effectively promoting the formation of a good interface with the subsequent matrix resin to obtain a high mechanical conversion effect.
[0057] The present invention can prepare a new generation of carbon fiber products with comprehensive advantages of strength and modulus through the improvement of the overall process, laying a foundation for the subsequent application of a new generation of composite materials in a wider range of multi-technical fields and multi-composite molding process systems. DETAILED DESCRIPTION
[0058] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0059] The embodiment of the present invention provides a method for preparing polyacrylonitrile-based carbon fiber, comprising the following steps:
[0060] S1. Aggregation
[0061] A polymerization reaction is carried out with acrylonitrile as the main monomer to obtain a polymerization stock solution, and the polymerization stock solution is subjected to demonification and degassing to obtain a spinning polymerization solution for use in the subsequent spinning process.
[0062] In some embodiments, the preparation process of the polymerization stock solution includes: mixing and dissolving the first monomer and the second monomer, performing a polymerization reaction in the presence of an initiator, and controlling the polymerization system temperature to 60-80° C. to promote sufficient polymerization. Specifically, the polymerization system temperature can be 60° C., 70° C., 80° C., etc., and is controlled in a temperature range within this range.
[0063] Further, the first monomer is acrylonitrile (AN), and the second monomer is selected from at least one of itaconic acid, sodium methacrylic acid sodium sulfonate, sodium methacrylic acid benzene sulfonate, vinyl acetate, methyl methacrylate, methyl acrylate, acrylamide, isopropanol, dithioester and n-octyl mercaptan, and can be one or more. The mass ratio of the amount of the first monomer to the total amount of monomers is 95-99:100, such as 95:100, 96:100, 97:100, 98:100, 99:100, etc., that is, the mass proportion of acrylonitrile is 95-99%, and the mass proportion of other components is 1-5%. The addition of the polymer component to the components other than acrylonitrile is mainly to optimize the viscoelastic properties of the polymer solution by introducing new groups, improve the processability of the polymer solution, etc.
[0064] Furthermore, the initiator is selected from at least one of initiators containing nitrogen-nitrogen double bonds such as azobisisobutyronitrile and azobisisoheptylnitrile, and the solvent used for dissolution is selected from one of dimethyl sulfoxide, dimethylformamide, dimethylacetamide, and zinc dichloride. The initiator and the solvent can be selected from the above raw materials, one or more of which can be selected. Preferably, the initiator is azobisisobutyronitrile and the solvent is dimethyl sulfoxide.
[0065] In some embodiments, the polymerization adopts a three-reactor linkage continuous polymerization process, and the sizes of the polymerization reactors are 10 to 25 m 3 10~25m 3 and 5~15m 3, control the total polymerization time of the three reactors to be 600-1300min (such as 600min, 700min, 800min, 900min, 1000min, 1100min, 1200min, 1300min, etc.). The three-reactor linkage means that the added materials pass through the three reactors in sequence. The first reactor continues to add raw materials while the third reactor continues to output the reacted materials. After testing: the polymerization stock solution output by the third reactor meets the following requirements: the solid content of the polymerization liquid is 20-23wt%, the rotational viscosity is 100000-150000cP, the weight average molecular weight is 250,000-300,000, the number average molecular weight is 100,000-130,000, the molecular weight distribution is 1.9-2.8, and the characteristic viscosity is 2.1-2.5dL / g.
[0066] It should be noted that the spinning solution of high molecular weight and narrow distribution system is conducive to the formation of reasonable precursor structure, and is also conducive to the regularization of the final carbon fiber structure, and has a positive effect on improving the strength and modulus of carbon fiber. However, after the molecular weight is increased, the viscosity of the spinning solution becomes higher, which will have a certain impact on the coagulation molding, and is not conducive to obtaining a homogeneous and highly oriented precursor. In addition, the basic viscoelastic and rheological properties of the polymer solution also have an important influence on the spinning molding and the acquisition of the oriented structure.
[0067] In view of the high shear and high draft characteristics of dry-jet wet spinning, the polymerization system of the present invention is designed to increase the molecular weight while adopting an appropriate monomer concentration. Through efficient heat and mass transfer control, the physical entanglement of the polyacrylonitrile molecular chain in the solution is reduced to facilitate the axial stretching of the molecular chain during shearing. At the same time, other components are used to optimize the viscoelastic properties of the polymerization solution and improve its viscosity, etc., thereby providing conditions for the construction of the final original fiber orientation structure.
[0068] In certain embodiments, the polymerization stock solution is subjected to the process of taking off single and deaeration by contacting the polymerization stock solution with a solvent in countercurrent, and the monomer content in the polymerization liquid after taking off single is controlled to be 0-100ppm, and the polymerization liquid after deaeration has no visible bubbles. The solvent used for taking off single and deaeration can be consistent with the solvent used in the polymerization stage. In the actual operation process, the polymerization stock solution flows from top to bottom into the deaeration tower and the deaeration tower, and dimethyl sulfoxide contacts the polymerization stock solution in countercurrent from bottom to top. The top of the deaeration tower and the deaeration tower is vacuumized, and the pressure in the tower of the deaeration tower and the deaeration tower is controlled to be 0-2KPa, such as 0.5KPa, 1KPa, 2KPa, etc. By the fine control of the deaeration process, high-quality homogeneous polymerization liquid is obtained to the maximum extent, and gels, impurities, etc. that form defects of the original silk structure are reduced.
[0069] S2. Spinning
[0070] The homogeneous polymer solution is spun by the dry-jet wet forming process to obtain spun fibers, and the spun fibers are washed, hot water drawn, dried, steam drawn and oiled in sequence to obtain fiber precursors. By selecting the spinning process and introducing technical links such as hot water drawing and steam drawing, the strength of the final carbon fiber can be significantly improved, which is conducive to obtaining high-denier, high-oriented and low-defect precursors, and finally achieving the strength, modulus characteristics and structural characteristics of carbon fiber-specific polyacrylonitrile precursors required by the design.
[0071] In some embodiments, the preparation process of the spun fiber includes: ejecting a homogeneous polymer solution from a combined spinneret, first passing through an air section and then passing through a multi-stage coagulation bath to complete the dry-jet wet spinning process. Air layer drafting is the most important feature that distinguishes dry-jet wet spinning from traditional wet spinning. In view of the characteristics of the first drafting orientation and subsequent phase separation and crystallization of the molecular chains in the solution stream after shearing and extrusion, the external force field matching is reasonably designed to maximize the formation of a regular orientation structure in the amorphous region that is easier to achieve characteristic structural inheritance during the pre-oxidation process. This stage is used to construct a reasonable heritable orientation structure, which is conducive to obtaining high modulus carbon fibers.
[0072] Furthermore, the temperature of the homogeneous polymer liquid for spinning is 50-60°C, the homogeneous polymer liquid is extruded and filtered, and then sprayed out from the spinning plate, the height of the air section is 2-6mm, and the air layer draft ratio is 2.5-4.0; the pore size of the spinneret is controlled to be 0.06-0.09mm, the pore spacing is 0.3-0.5mm, the aspect ratio of the spinneret hole is 2-3, and the shape of the spinneret is spherical or flat.
[0073] It should be noted that the spinning plate can be a 3K / 4K / 6K combined spinneret, through which the spinneret of 3K, 6K, 12K, 24K and other specifications can be realized, and the number of spinneret holes is 1-20 more than the designed K number, such as the number of 3K spinneret holes is 3001-3020. The spinneret hole diameter can be 0.06mm, 0.07mm, 0.08mm, 0.09mm, etc., the hole spacing is 0.3mm, 0.4mm, 0.5mm, etc., and the spinneret hole aspect ratio can be 2, 2.5, 3.0, etc.
[0074] Specifically, the temperature of the homogeneous polymer solution can be 50°C, 55°C, 60°C, etc. After the homogeneous polymer solution is extruded by a metering pump, it is filtered through a filter and then ejected from a spinneret. The metering pump capacity can be 40-60cc / r, the number of gears can be 2-3, and the number of teeth can be 20-30; the filter can be a metal sintered felt type with an accuracy of 2-4μm. After being ejected, the polymer solution first passes through an air layer, the height of the air segment can be 2mm, 3mm, 4mm, 5mm, 6mm, etc., and the air layer draft ratio can be 2.5, 3.0, 3.5, 4.0, etc.
[0075] Furthermore, the multi-stage coagulation bath includes at least the first coagulation bath and the second coagulation bath, and each coagulation bath is a mixed solution formed by an organic solvent and water. The water content gradually increases from the first coagulation bath to the last coagulation bath, and the organic solvent is the same type of solvent used in the polymerization stage. Each coagulation bath uses alkaline solution to adjust the pH value to 8-10 (such as 8, 9, 10, etc.). Water is a coagulant in the coagulation bath that can coagulate the spinning. It is advisable to control the water content to gradually increase to prevent too fast coagulation from affecting product performance. Specifically, the type of organic solvent in the coagulation bath is the same as the solvent used in the polymerization stage.
[0076] In some embodiments, the mass fraction of the organic solvent in the first coagulation bath is 60-78% (such as 60%, 65%, 70%, 75%, 78%, etc.), the temperature is 40-60°C (such as 40°C, 50°C, 60°C, etc.), and the draft ratio is 1.0-2.0 (such as 1.0, 1.5, 2.0, etc.); the mass fraction of the organic solvent in the second coagulation bath is 15-45% (such as 15%, 20%, 30%, 40%, 45%, etc.), the temperature is 50-70°C (such as 50°C, 60°C, 70°C, etc.), and the draft ratio is 1.0-2.0 (such as 1.0, 1.5, 2.0, etc.). A third coagulation bath and a fourth coagulation bath can also be added as needed. Specifically, the alkali solution used to adjust the pH value of each coagulation bath can be sodium bicarbonate, ammonium bicarbonate, ammonia water, etc.
[0077] It should be noted that a high molecular weight narrow distribution polymer solution is subjected to a coagulation bath under high temperature and concentration conditions to obtain a precursor with high orientation and crystallinity. The crystallinity and orientation of the precursor can be effectively adjusted by the coagulation temperature, concentration and pH value to obtain excellent comprehensive performance. Adjusting the coagulation environment mainly includes the concentration and temperature of the coagulation bath, controlling the matching of the diffusion coefficient and the diffusion rate in the double diffusion process, achieving the orderly arrangement of the molecular chains, the reasonable formation of the crystalline structure and the homogeneous and dense morphology structure, so as to achieve the purpose of reducing the probability of defects in the fiber. In addition, homogeneous coagulation control, especially controlling the stability of the coagulation bath surface, preventing condensation and preventing overflow, etc., can achieve the stabilization and homogenization of fiber quality.
[0078] Further, the spun fiber is washed with water for multiple stages, and then hot water stretched at 80-95°C (such as 80°C, 85°C, 90°C, 95°C, etc.), and then steam stretched at 130-160°C (such as 130°C, 140°C, 150°C, 160°C, etc.) after drying, and then oiled and heat-set to obtain fiber precursors; the fiber precursors are controlled to meet the following requirements: the fiber single filament fineness is 0.70-0.90 dtex (such as 0.70 dtex, 0.80 dtex, 0 .90dtex, etc.), single yarn strength 8.0-10.0cN / dtex (such as 8.0cN / dtex, 9.0cN / dtex, 10.0cN / dtex, etc.), single yarn modulus 95-135cN / dtex (such as 95cN / dtex, 100cN / dtex, 110cN / dtex, 120cN / dtex, 130cN / dtex, 135cN / dtex, etc.), bulk density 1.18-1.19g / cm 3 (For example, it can be 1.18g / cm 3 , 1.19g / cm 3 wait).
[0079] The specific parameter control of hot water drawing and steam drawing is to obtain fiber precursors that meet the above requirements. Specifically, hot water drawing is to control the drawing ratio to 2.0-4.0 (such as 2.0, 3.0, 4.0, etc.), and steam drawing is to operate with saturated steam, control the steam force to 3.0-8.0 bar (such as 3.0 bar, 4.0 bar, 5.0 bar, 6.0 bar, 7.0 bar, 8.0 bar, etc.), and the steam drawing ratio is 2.0-5.0 (such as 2.0, 3.0, 4.0, 5.0, etc.). Steam drawing can significantly improve the crystallinity and orientation of the fiber, which is helpful to produce high-performance carbon fiber precursors.
[0080] Furthermore, the multi-stage washing is carried out in 5-10 stages, each stage of washing corresponds to a washing tank and two sets of traction rollers, so that the fiber contacts the water flow in reverse direction, and the washing temperature is controlled to be 50-85°C, and the washing temperature can be 50°C, 60°C, 70°C, 80°C, 85°C, etc. In actual operation, during the multi-stage washing, the fiber can be controlled to move from front to back and the water flow can be controlled to move from back to front.
[0081] Furthermore, after hot water drawing, drying is performed using saturated steam, the steam pressure of the saturated steam is controlled to be 1.5-10 bar, a step-type pressure gradient design is adopted, the pressure is gradually increased, and the number of drying rollers is 15-30. Specifically, the steam pressure can be 1.5 bar, 3.0 bar, 5.0 bar, 7.0 bar, 9.0 bar, 10.0 bar, etc., and the number of drying rollers can be 15, 20, 25, 30, etc.
[0082] It should be emphasized that the temperature, time and tension (drawing ratio) in hot water drawing, especially steam drawing, ensure the fine denier of the precursor, so as to improve the strength of the fiber, especially the final carbon fiber. In addition, the temperature and time of the drying and densification process are regulated to eliminate the internal stress and defects caused by the movement of macromolecules, and further eliminate the structural unevenness caused by the mutual diffusion of solvents and coagulants to obtain high-denier, high-orientation and low-defect precursors, and finally achieve the strength, modulus characteristics and structural characteristics of carbon fiber-specific polyacrylonitrile precursors that meet the design requirements.
[0083] In some embodiments, the oiling solution used in the oiling process includes, by weight, 60-75 parts of water, 15-20 parts of silicone oil, 5-10 parts of emulsifier, 1-5 parts of penetrant and 1-5 parts of antistatic agent; the overall oiling rate is controlled to be 1.0-2.5wt% (e.g., 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, etc.). The type of oiling solution is not limited to the above formula, and other existing oiling solution formulas can be used, which are not limited here.
[0084] Furthermore, the oil agent is selected from at least one of dimethyl silicone oil and amino silicone oil, and can be one or more. The emulsifier is a nonionic surfactant, such as isomeric alcohol polyoxyethylene ether, fatty acid polyoxyethylene ether, etc., and can be any one or more of the above. The penetrant is selected from at least one of alkyl sulfonates, quaternary ammonium salts and aliphatic ethers, and can be any one or more of the above. The antistatic agent is at least one of anionic, cationic and nonionic; the anionic type is selected from at least one of alkyl sulfonates, carboxylates and phosphates; the cationic type is selected from at least one of quaternary ammonium salts; the nonionic type is selected from at least one of alkanolamides, polyethylene glycol stearate, polyols and stearic acid polyglycerol esters.
[0085] S3, pre-oxidation, carbonization
[0086] The fiber precursor is sequentially pretreated, pre-oxidized, and carbonized in multiple stages to obtain carbonized fiber. Appropriate drawing during the pre-oxidation process is beneficial to improving the mechanical properties of the carbon fiber.
[0087] In the actual operation process, the pretreatment is to immerse the fiber precursor in the pretreatment solution, and the pretreatment time is 10-15s (such as 10s, 13s, 15s, etc.). The pretreatment solution includes 96-99 parts of water, 1-2 parts of oil, 0.01-0.2 parts of modifier and 0.01-0.2 parts of pre-oxidation promoter by mass. Among them, the oil is a modified polysiloxane, preferably, the oil is selected from at least one of amino-modified polysiloxane, polyether-modified polysiloxane and epoxy-modified polysiloxane, and can be one or more; the modifier is selected from at least one of boric acid, metaboric acid, tetraboric acid and boric acid ester, and can be any one or more of the above; the pre-oxidation promoter is a peroxide, and the peroxide is selected from at least one of cumene hydroperoxide and di-tert-butyl peroxide, and the above peroxides are suitable as pre-oxidation promoters.
[0088] In another embodiment, the pretreatment solution further comprises 0.5-1 part of an emulsifier, and the emulsifier is selected from at least one of nonylphenol polyoxyethylene ether and fatty alcohol polyoxyethylene ether.
[0089] Further, after the fiber precursor is pretreated, it is sequentially subjected to pre-oxidation and multi-stage carbonization. The pre-oxidation is divided into 4-6 oxidation zones for treatment. The starting temperature of the oxidation zone is controlled to be 180-220°C (such as 180°C, 190°C, 200°C, 210°C, 220°C, etc.), and the ending temperature is 245-270°C (such as 245°C, 250°C, 260°C, 270°C, etc.). The draft ratio of each temperature zone is 0.9-1.3 (such as 0.9, 1.1, 1.2, 1.3, etc.), and the pre-oxidation yarn density is controlled to be 1.33-1.36g / cm 3 (e.g. 1.33 g / cm 3 , 1.34g / cm 3 , 1.35g / cm 3 , 1.36g / cm 3 Applying drafting can eliminate the gaps between molecules to a certain extent, inhibit fiber shrinkage, and increase the preferential orientation of the main chain structure to the fiber axis.
[0090] It should be noted that the pre-oxidation process parameters mainly include pre-oxidation temperature and its distribution gradient, speed (pre-oxidation time), draft ratio, etc. Pre-oxidation temperature and its distribution are key process parameters that affect the degree of fiber pre-oxidation, which in turn affects the mechanical properties of carbon fiber such as tensile strength and modulus. If the pre-oxidation temperature is too high, it will cause over-oxidation of PAN fiber, destroy the molecular structure of the ladder polymer, limit the formation of carbon-based plane length and stacking height in the carbonization stage, and produce a skin-core structure in the radial direction of the fiber; if the pre-oxidation temperature is too low, the pre-oxidation is insufficient, and the pre-oxidized fiber is prone to melting during the carbonization stage, resulting in reduced carbon fiber performance.
[0091] Furthermore, the multi-stage carbonization is carried out in sequence of low temperature carbonization, high temperature carbonization and ultra-high temperature carbonization, and the operating parameters of each stage are as follows:
[0092] The starting temperature of low temperature carbonization is 350°C-420°C, the ending temperature is 700°C-850°C, and the drawing ratio is 1.0-1.15. Specifically, the starting temperature of low temperature carbonization can be 350°C, 370°C, 400°C, 420°C, etc., the ending temperature can be 700°C, 750°C, 800°C, 850°C, etc., and the drawing ratio can be 1.0, 1.05, 1.10, 1.15, etc.
[0093] The starting temperature of high temperature carbonization is 900°C-1200°C, the ending temperature is 1350°C-1450°C, and the drawing ratio is 0.95-1.0. Specifically, the starting temperature of high temperature carbonization can be 900°C, 1000°C, 1100°C, 1200°C, etc., the ending temperature can be 1350°C, 1400°C, 1450°C, etc., and the drawing ratio can be 0.95, 0.98, 1.00, etc.
[0094] Ultra-high temperature carbonization is to control the carbonization temperature to be 1600°C-2300°C, and the draw ratio to be 1.0-1.1. Specifically, the carbonization temperature of ultra-high temperature carbonization can be 1600°C, 1800°C, 2000°C, 2300°C, etc., and the draw ratio can be 1.0, 1.1, etc.
[0095] The three-stage carbonization process can be carried out under a nitrogen atmosphere, and other inert atmospheres can be used.
[0096] It should be noted that the carbonization temperature is the main factor affecting the structural transformation and performance of polyacrylonitrile fibers during the carbonization process. During the low-temperature carbonization process, the fibers are pyrolyzed in large quantities, causing the original orientation to be deoriented, and a large number of pores are formed, resulting in a decrease in the mechanical properties of the fibers. In order to suppress the disorder caused by pyrolysis, it is necessary to apply stretching to them, thereby improving the orientation and crystallinity of the fibers; at the same time, the pores in the fibers are oriented along the fiber axis under the stretching tension, and the shape becomes a needle-shaped hole, which can be further merged or even eliminated, thereby improving the mechanical properties of the fibers. During the high-temperature carbonization process, the small carbon mesh plane of the fiber is thermally condensed into a large carbon mesh plane, resulting in chemical shrinkage. At this stage, negative stretching is generally applied to inhibit its free shrinkage and maintain the preferential orientation of the carbon mesh plane to the fiber axis; excessive stretching can cause the fiber to break or partially damage to generate hair, affecting the mechanical properties of the fiber. In short, applying tension stretching during the carbonization process is beneficial to improving the mechanical properties of carbon fiber, but different stretching needs to be implemented for different temperature sections in the process.
[0097] S4. Surface treatment
[0098] The carbonized fiber is subjected to anodizing electrochemical surface treatment to produce functional groups such as carboxyl and hydroxyl groups on the fiber surface, so as to form better chemical bonding, i.e., interface bonding effect, with a matrix such as epoxy resin during subsequent fiber application.
[0099] In some embodiments, the carbonized fiber is surface treated by electrolytic oxidation, and the current density is controlled to be 0.5-1.5A / m 2 , the treatment time is 50-90s, and the electrolyte temperature is 20-35°C. Specifically, the current density can be 0.5A / m 2 , 1.0A / m 2 , 1.5A / m 2 etc., the processing time can be 50s, 60s, 70s, 80s, 90s, etc., and the electrolyte temperature can be 20°C, 25°C, 30°C, 35°C, etc.
[0100] Furthermore, the electrolyte is selected from at least one of ammonium bicarbonate solution, sodium bicarbonate solution and ammonium nitrate solution, and the concentration of the electrolyte is 3-6wt%, such as 3wt%, 4wt%, 5wt%, 6wt% and the like.
[0101] In some embodiments, an ultrasonic generator is installed on the surface treatment tank to irradiate the carbonized fiber with ultrasound, and the ultrasound frequency is controlled to be 60-120kHz and the ultrasound intensity is 4-8W / cm 2 Ultrasonic assisted strengthening during the surface treatment process is beneficial to achieve the purpose of strengthening the anodized surface treatment of carbon fiber and uniform oxidation of the inner and outer monofilaments of the carbon fiber tow. Specifically, the ultrasonic frequency can be 60kHz, 80kHz, 100kHz, 120kHz, etc., and the ultrasonic intensity can be 4W / cm 2 、6W / cm 2 , 8W / cm 2 wait.
[0102] S5. Sizing
[0103] The surface treated carbon fiber is washed, sized and dried in sequence. The residual ammonium bicarbonate and other substances on the surface are removed by washing. The sizing is performed by adding thermoplastic materials to optimize the thermosetting formula system of the sizing agent, so as to increase the flexibility of the carbon fiber after sizing and reduce the fuzz formed by brittle breakage. At the same time, it has good fiber opening and bundling properties to meet the needs of subsequent applications.
[0104] In some embodiments, the sizing agent includes, by mass fraction, 20-40 parts of epoxy resin, 20-40 parts of polyester resin, 10-20 parts of emulsifier and 1-5 parts of sizing agent; the emulsifier is selected from at least one of fatty acid and fatty alcohol polyoxyethylene ether; the sizing agent is selected from at least one of polyurethane and polyamide; and the composition of the sizing agent is optimized to further increase the flexibility of the carbon fiber.
[0105] Furthermore, during the sizing process, the sizing amount of the sizing agent is controlled to be 1-2wt%, such as 1wt%, 1.5wt%, 2.0wt%, etc.
[0106] Furthermore, after sizing, drying is performed, and the drying temperature is controlled to be 150-190° C., such as 150° C., 160° C., 170° C., 180° C., 190° C., etc., and the drying method can be hot air drying.
[0107] The embodiment of the present invention also provides a polyacrylonitrile-based carbon fiber, which is prepared by the above preparation method and has the advantages of high strength and high modulus.
[0108] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0109] Example 1
[0110] This embodiment provides a method for preparing polyacrylonitrile-based carbon fiber, comprising the following steps:
[0111] (1) Aggregation
[0112] The mass percentage of the polymerization ingredients is acrylonitrile: itaconic acid: methyl acrylate = 97:1:2, the initiator is azobisisobutyronitrile, and the solvent is dimethyl sulfoxide. After the raw materials are mixed and dissolved, a continuous polymerization process is carried out, and the three reactors are linked. The total polymerization reaction time is 850 minutes to obtain a polymerization liquid. Among them, the total amount of polymerization monomers is 20%, the amount of initiator is 0.2%, and the amount of solvent is 79.8%. The sizes of the three reactors are 20m 3 、20m 3 、10m 3 .
[0113] The main properties of the polymer liquid are: solid content 21%, rotational viscosity 120000 cP, number average molecular weight 110,000, weight average molecular weight 260,000, molecular weight distribution 2.2, and intrinsic viscosity 2.3.
[0114] The polymerization stock solution flows into the desing tower and the degassing tower from top to bottom, and dimethyl sulfoxide flows countercurrently from bottom to top. The top of the tower is vacuumed and the pressure in the tower is controlled to be 1KPa.
[0115] (2) Spinning
[0116] After de-spinning and degassing, the dry-jet wet spinning process is used for spinning. After precise metering and filtration, the spinning is carried out. The polymer liquid is ejected from the combined spinneret, first passes through the air section, and then goes through a multi-stage coagulation bath, water washing, hot water drawing, drying and densification, steam drawing, oiling, and heat setting.
[0117] The spinneret assembly is 12K, the spinneret aperture is 0.08mm, the hole spacing is 0.4mm, the spinneret material is tantalum, the shape is spherical, and the spinneret aperture aspect ratio is 3; the air layer height is set to 3mm, and the air layer draft ratio is 3.0. The temperature of the spinning polymer solution is 50°C, the temperature of the first coagulation bath is 50°C, the concentration of dimethyl sulfoxide in the coagulation bath is 75% (mass fraction, the same below), and the draft ratio is 1.5; the temperature of the second coagulation bath is 60°C, the concentration of dimethyl sulfoxide in the second coagulation bath is 35%, and the draft ratio is 1.2. Sodium bicarbonate is used to adjust the pH value of the first coagulation bath and the second coagulation bath to 9.
[0118] After the first coagulation bath and the second coagulation bath, water washing is performed to remove residual dimethyl sulfoxide in the raw silk. The water washing temperature is set at 60°C, the hot water drawing temperature is set at 90°C, and the drawing ratio is 2.5. The steam pressure of the saturated steam for drying and densification starts at 2.0 bar and ends at 9.0 bar. The pressure gradient is designed, and the number of drying rollers is 20. After drying and densification, steam drawing is performed, saturated steam, the steam drawing pressure is 5.2 bar, the temperature is 155°C, and the drawing ratio is 4.0. After that, the raw silk is oiled. The oiling solution used in the oiling process includes: 70 parts of water, 18 parts of aminosilicon, 8 parts of emulsifier (fatty acid polyoxyethylene ether), 3 parts of penetrant (sodium dioctyl sulfonated succinate) and 3 parts of antistatic agent (polyethylene glycol stearate); the oiling rate is 1.6%.
[0119] The main performance indicators of the raw silk are: single yarn strength 9.5cN / dtex, single yarn modulus 120cN / dtex, bulk density 1.190g / cm 3 .
[0120] (3) Pre-oxidation and carbonization
[0121] The raw silk is firstly pretreated with a pretreatment solution, and then pre-oxidation, low-temperature carbonization, high-temperature carbonization and ultra-high-temperature carbonization are sequentially performed.
[0122] The pretreatment solution contains an oil agent (main component epoxy-modified polysiloxane), a modifier boric acid, and a pre-oxidation accelerator di-tert-butyl peroxide, etc. The pretreatment time is 12 seconds.
[0123] The starting temperature of pre-oxidation is 185℃, the ending temperature is 250℃, the pre-oxidation is carried out in air atmosphere in 6 temperature zones, and the density of pre-oxidized wire is 1.349g / cm 3 .
[0124] The starting temperature of the low temperature carbonization furnace is 410℃, the highest temperature is 850℃, 6 temperature zones, nitrogen atmosphere, and the draw ratio is 1.07. The starting temperature of the high temperature carbonization furnace is 1000℃, the ending temperature is 1400℃, nitrogen atmosphere, and the draw ratio is 0.983. The temperature of the ultra-high temperature furnace is 1690℃, nitrogen atmosphere, and the draw ratio is 1.002.
[0125] (4) Surface treatment
[0126] The carbon fiber surface was treated by anodic oxidation (electrolytic oxidation) method, with NH4HCO3 solution as the electrolyte, the electrolyte concentration was 5wt%, and the current density was 1.0A / m 2 , time 60s, temperature 30℃, surface treatment voltage 9.4V. Ultrasonic assisted strengthening was performed during the surface treatment process. An ultrasonic generator was installed on the surface treatment tank to radiate ultrasonic waves on the carbon fiber. The ultrasonic frequency was 100kHz and the ultrasonic intensity was 6W / cm 2 , processing time 70s.
[0127] (5) Sizing
[0128] The main components of the sizing agent are epoxy resin, emulsifier fatty alcohol polyoxyethylene ether, sizing agent polyurethane, and the carbon fiber sizing agent content is 1.4%. After sizing, hot air drying is carried out at a drying temperature of 170°C.
[0129] After testing: the tensile strength of carbon fiber multifilament is 7185MPa, the tensile modulus is 322Gpa, and the elongation at break is 2.2%.
[0130] Example 2
[0131] This embodiment provides a method for preparing polyacrylonitrile-based carbon fiber, comprising the following steps:
[0132] (1) Aggregation
[0133] Same as Example 1.
[0134] (2) Spinning
[0135] Same as Example 1.
[0136] (3) Pre-oxidation and carbonization
[0137] The raw silk is firstly pretreated with a pretreatment solution, and then pre-oxidation, low-temperature carbonization, high-temperature carbonization and ultra-high-temperature carbonization are sequentially performed.
[0138] The pretreatment solution includes an oil agent (main component epoxy-modified polysiloxane), a modifier boric acid, and a pre-oxidation accelerator di-tert-butyl peroxide, etc. The pretreatment time is 12 seconds.
[0139] The starting temperature of pre-oxidation is 184℃, the ending temperature is 252℃, the pre-oxidation is carried out in 6 temperature zones with air atmosphere, and the density of pre-oxidized wire is 1.353g / cm 3 .
[0140] The starting temperature of the low temperature carbonization furnace is 370℃, the highest temperature is 770℃, 6 temperature zones, nitrogen atmosphere, and the draw ratio is 1.07. The starting temperature of the high temperature carbonization furnace is 1050℃, the ending temperature is 1450℃, nitrogen atmosphere, and the draw ratio is 0.983. The temperature of the ultra-high temperature furnace is 1820℃, nitrogen atmosphere, and the draw ratio is 1.001.
[0141] (4) Surface treatment
[0142] The carbon fiber surface was treated by anodic oxidation (electrolytic oxidation) method, with NH4HCO3 solution as the electrolyte, the electrolyte concentration was 5wt%, and the current density was 1.0A / m 2 , time 60s, temperature 30℃, surface treatment voltage 9.4V. Ultrasonic assisted strengthening was performed during the surface treatment process. An ultrasonic generator was installed on the surface treatment tank to radiate ultrasonic waves on the carbon fiber. The ultrasonic frequency was 100kHz and the ultrasonic intensity was 6W / cm 2 , processing time 70s.
[0143] (5) Sizing
[0144] The main components of the sizing agent are epoxy resin, emulsifier fatty alcohol polyoxyethylene ether, sizing agent polyurethane, and the carbon fiber sizing agent content is 1.0%. After sizing, hot air drying is performed at a drying temperature of 170°C.
[0145] After testing: the tensile strength of carbon fiber multifilament is 6756MPa, the tensile modulus is 347Gpa, and the elongation at break is 1.9%.
[0146] Example 3
[0147] This embodiment provides a method for preparing polyacrylonitrile-based carbon fiber, comprising the following steps:
[0148] (1) Aggregation
[0149] Same as Example 1.
[0150] (2) Spinning
[0151] Same as Example 1.
[0152] (3) Pre-oxidation and carbonization
[0153] The raw silk is firstly pretreated with a pretreatment solution, and then pre-oxidation, low-temperature carbonization, high-temperature carbonization and ultra-high-temperature carbonization are sequentially performed.
[0154] The pretreatment solution includes an oil agent (main component epoxy-modified polysiloxane), a modifier boric acid, and a pre-oxidation accelerator di-tert-butyl peroxide, etc. The pretreatment time is 12 seconds.
[0155] The starting temperature of pre-oxidation is 184℃, the ending temperature is 254℃, the pre-oxidation is carried out in 6 temperature zones with air atmosphere, and the density of pre-oxidized wire is 1.360g / cm 3 .
[0156] The starting temperature of the low temperature carbonization furnace is 370℃, the highest temperature is 770℃, 6 temperature zones, nitrogen atmosphere, and the draw ratio is 1.06. The starting temperature of the high temperature carbonization furnace is 1100℃, the ending temperature is 1450℃, nitrogen atmosphere, and the draw ratio is 0.978. The temperature of the ultra-high temperature furnace is 2100℃, nitrogen atmosphere, and the draw ratio is 1.0085.
[0157] (4) Surface treatment
[0158] The carbon fiber surface was treated by anodic oxidation (electrolytic oxidation) method, with NH4HCO3 solution as the electrolyte, the electrolyte concentration was 5wt%, and the current density was 1.0A / m 2 , time 60s, temperature 30℃, surface treatment voltage 9.5V. Ultrasonic assisted strengthening was performed during the surface treatment process. An ultrasonic generator was installed on the surface treatment tank to radiate ultrasonic waves on the carbon fiber. The ultrasonic frequency was 100kHz and the ultrasonic intensity was 6W / cm 2 , processing time 70s.
[0159] (5) Sizing
[0160] The main components of the sizing agent are epoxy resin, emulsifier fatty alcohol polyoxyethylene ether, sizing agent polyurethane, and the carbon fiber sizing agent content is 1.2%. After sizing, hot air drying is performed at a drying temperature of 170°C.
[0161] After testing: the tensile strength of carbon fiber multifilament is 5938MPa, the tensile modulus is 383Gpa, and the elongation at break is 1.55%.
[0162] Comparative Example 1
[0163] The only difference from Example 1 is that the raw silk is prepared by the traditional wet spinning process, and the other parameters are the same as those in Example 1.
[0164] After testing: the tensile strength of carbon fiber multifilament is 5638MPa, the tensile modulus is 313Gpa, and the elongation at break is 1.80%.
[0165] Comparative Example 2
[0166] The raw silk was prepared by a conventional wet spinning process, and other parameters were the same as those in Example 2.
[0167] After testing: the tensile strength of carbon fiber multifilament is 5369MPa, the tensile modulus is 341Gpa, and the elongation at break is 1.57%.
[0168] Comparative Example 3
[0169] The carbonization process was reduced by 15% compared with the example 1, and other parameters were the same as those in example 1.
[0170] After testing: the tensile strength of carbon fiber multifilament is 6283MPa, the tensile modulus is 315Gpa, and the elongation at break is 1.99%.
[0171] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing polyacrylonitrile-based carbon fiber, characterized in that: include: A continuous polymerization reaction is carried out with acrylonitrile as the main monomer to obtain a polymerization stock solution, and the polymerization stock solution is subjected to demonstration and degassing to obtain a homogeneous polymerization solution; The homogeneous polymer solution is spun by a dry-wet-jet forming process to obtain spun fibers, and the spun fibers are sequentially washed, hot-water drawn, dried, steam drawn and oiled to obtain fiber precursors; The fiber precursor is sequentially pretreated, preoxidized, and carbonized in multiple stages to obtain carbonized fiber; The carbonized fiber is subjected to surface treatment, water washing, sizing and drying in sequence, wherein the surface treatment is carried out by electrolytic oxidation; The preparation process of the spun fiber comprises: the homogeneous polymer solution is ejected from a combined spinneret, first passes through an air section and then passes through a multi-stage coagulation bath; the temperature of the homogeneous polymer solution for spinning is 50-60° C., the homogeneous polymer solution is extruded and filtered, and then ejected from a spinning plate, the height of the air section is 2-6 mm, and the air layer draft ratio is 2.5-4.0; the pore size of the spinneret is controlled to be 0.06-0.09 mm, the pore spacing is 0.3-0.5 mm, the spinneret hole aspect ratio is 2-3, and the shape of the spinneret is spherical or flat; The spun fibers are washed with water for multiple stages, then stretched with hot water at 80-95°C, and then steam stretched at 130-160°C after drying, and then oiled and heat-set to obtain the fiber precursors; the fiber precursors are controlled to meet the following requirements: The original single fiber fineness is 0.70-0.90dtex, the single fiber strength is 8.0-10.0cN / dtex, the single fiber modulus is 95-135cN / dtex, and the bulk density is 1.18-1.19g / cm 3 ; Hot water drawing is to control the drawing ratio to 2.0-4.0, and steam drawing is to operate with saturated steam, controlling the steam force to 3.0-8.0 bar, and the steam drawing ratio to 2.0-5.0; The multi-stage washing is divided into 5-10 stages. Each stage of washing corresponds to a washing tank and two sets of traction rollers, so that the fiber contacts the water flow in reverse direction. The washing temperature is controlled at 50-85℃. After hot water drawing, drying is done with saturated steam. The steam pressure of the saturated steam is controlled at 1.5-10 bar. A stepped pressure gradient design is adopted, and the number of drying rollers is 15-30. After the fiber precursor is pretreated, it is pre-oxidized and multi-stage carbonized in sequence. The pre-oxidation is divided into 4-6 oxidation zones for treatment. The starting temperature of the oxidation zone is controlled to be 180-220°C, the ending temperature is controlled to be 245-270°C, the draft ratio of each temperature zone is 0.9-1.3, and the pre-oxidized yarn density is controlled to be 1.33-1.36g / cm 3 ; Multi-stage carbonization is to carry out low-temperature carbonization, high-temperature carbonization and ultra-high-temperature carbonization in sequence. The starting temperature of low-temperature carbonization is 350℃-420℃, the ending temperature is 700℃-850℃, and the drawing ratio is 1.0-1.15; the starting temperature of high-temperature carbonization is 900℃-1200℃, the ending temperature is 1350℃-1450℃, and the drawing ratio is 0.95-1.0; ultra-high-temperature carbonization is to control the carbonization temperature to 1600℃-2300℃, and the drawing ratio is 1.0-1.1; The pretreatment is to immerse the fiber precursor in a pretreatment solution for 10-15 seconds. The pretreatment solution comprises 96-99 parts of water, 1-2 parts of oil, 0.01-0.2 parts of modifier and 0.01-0.2 parts of preoxidation accelerator by weight. Wherein, the oil agent is a modified polysiloxane; The modifier is selected from at least one of boric acid, metaboric acid, tetraboric acid and boric acid esters; The pre-oxidation accelerator is a peroxide, and the peroxide is selected from at least one of cumene hydroperoxide and di-tert-butyl peroxide.
2. The preparation method according to claim 1, characterized in that: The preparation process of the polymerization stock solution includes: mixing and dissolving the first monomer and the second monomer, performing a polymerization reaction in the presence of an initiator, controlling the polymerization system temperature to 60-80° C., and the total polymerization time to 600-1300 min; The first monomer is acrylonitrile, and the second monomer is selected from at least one of itaconic acid, sodium methyl methacrylate sulfonate, sodium methyl methacrylate benzene sulfonate, vinyl acetate, methyl methacrylate, methyl acrylate, acrylamide, isopropanol, dithioester and n-octyl mercaptan.
3. The preparation method according to claim 2, characterized in that: The mass ratio of the amount of the first monomer to the total amount of monomers is 95-99:
100.
4. The preparation method according to claim 2, characterized in that: The initiator is selected from at least one of azobisisobutyronitrile and azobisisoheptylnitrile, and the solvent used for dissolution is selected from one of dimethyl sulfoxide, dimethylformamide, dimethylacetamide and zinc dichloride.
5. The preparation method according to claim 2, characterized in that: The polymerization adopts a three-reactor linkage continuous polymerization process, and the sizes of the polymerization reactors are 10 to 25m 3 10~25m 3 and 5~15m 3 , the total polymerization time of the three reactors was controlled to be 600–1300 min.
6. The preparation method according to claim 2, characterized in that: The polymerization stock solution meets the following requirements: the solid content of the polymerization solution is 20-23wt%, the rotational viscosity is 100000-150000 cP, the weight average molecular weight is 250,000-300,000, the number average molecular weight is 100,000-130,000, the molecular weight distribution is 1.9-2.8, and the intrinsic viscosity is 2.1-2.5 dL / g.
7. The preparation method according to claim 1, characterized in that: The process of removing monomers and degassing the polymerization stock solution is to contact the polymerization stock solution with a solvent in countercurrent, and control the monomer content in the polymerization solution after the removal of monomers to be 0-100 ppm.
8. The preparation method according to claim 7, characterized in that: The tops of the de-singling tower and the de-bubbling tower are evacuated to control the pressure inside the de-singling tower and the de-bubbling tower to be 0-2KPa.
9. The preparation method according to claim 1, characterized in that: The multi-stage coagulation bath includes at least a first coagulation bath and a second coagulation bath. Each stage of the coagulation bath is a mixed liquid formed by an organic solvent and water. The water content gradually increases from the first coagulation bath to the last stage of the coagulation bath. The organic solvent is of the same type as the solvent used in the polymerization stage. Each stage of the coagulation bath uses alkaline solution to adjust the pH value to 8-10.
10. The preparation method according to claim 9, characterized in that: The mass fraction of the organic solvent in the first coagulation bath is 60-78%, the temperature is 40-60°C, and the drawing ratio is 1.0-2.0; the mass fraction of the organic solvent in the second coagulation bath is 15-45%, the temperature is 50-70°C, and the drawing ratio is 1.0-2.
0.
11. The preparation method according to claim 1, characterized in that: The oiling solution used in the oiling process includes, by weight, 60-75 parts of water, 15-20 parts of silicone oil, 5-10 parts of emulsifier, 1-5 parts of penetrant and 1-5 parts of antistatic agent, and the overall oiling rate is controlled to be 1.0-2.5wt%.
12. The preparation method according to claim 11, characterized in that: The silicone oil is selected from at least one of dimethyl silicone oil and amino silicone oil.
13. The preparation method according to claim 11, characterized in that: The emulsifier is a nonionic surfactant.
14. The preparation method according to claim 13, characterized in that: The emulsifier is selected from at least one of isomeric alcohol polyoxyethylene ether and fatty acid polyoxyethylene ether.
15. The preparation method according to claim 11, characterized in that: The penetrant is selected from at least one of alkyl sulfonates, quaternary ammonium salts and aliphatic ethers.
16. The preparation method according to claim 11, characterized in that: The antistatic agent is at least one of anionic, cationic and nonionic.
17. The preparation method according to claim 16, characterized in that: The anion type is selected from at least one of alkyl sulfonates, carboxylates and phosphates.
18. The preparation method according to claim 16, characterized in that: The cationic type is selected from at least one of quaternary ammonium salts.
19. The preparation method according to claim 16, characterized in that: The nonionic type is selected from at least one of alkanolamides, polyethylene glycol stearate, polyols and polyglycerol stearate.
20. The preparation method according to claim 1, characterized in that: The oil agent is selected from at least one of amino-modified polysiloxane, polyether-modified polysiloxane and epoxy-modified polysiloxane.
21. The preparation method according to claim 20, characterized in that: The pretreatment solution further comprises 0.5-1 part of an emulsifier, wherein the emulsifier is selected from at least one of nonylphenol polyoxyethylene ether and fatty alcohol polyoxyethylene ether.
22. The preparation method according to claim 1, characterized in that: The carbonized fiber is surface treated by electrolytic oxidation, and the current density is controlled to be 0.5-1.5A / m 2 The treatment time is 50-90s, the electrolyte temperature is 20-35°C, and the electrolyte is selected from at least one of ammonium bicarbonate solution, sodium bicarbonate solution and ammonium nitrate solution.
23. The preparation method according to claim 22, characterized in that: The concentration of the electrolyte is 3-6 wt %.
24. The preparation method according to claim 23, characterized in that: An ultrasonic generator is installed on the surface treatment tank to irradiate the carbonized fiber with ultrasound, and the ultrasonic frequency is controlled to be 60-120kHz and the ultrasonic intensity is 4-8W / cm 2 .
25. The preparation method according to claim 1, characterized in that: During the sizing process, the sizing amount of the sizing agent is controlled to be 1-2 wt %, and the sizing agent includes 20-40 parts of epoxy resin, 20-40 parts of polyester resin, 10-20 parts of emulsifier and 1-5 parts of sizing agent by mass fraction.
26. The preparation method according to claim 25, characterized in that: The emulsifier is selected from at least one of fatty acids and fatty alcohol polyoxyethylene ethers.
27. The preparation method according to claim 25, characterized in that: The sizing agent is selected from at least one of polyurethane and polyamide.
28. The preparation method according to claim 25, characterized in that: After sizing, the material is dried at a temperature of 150-190°C.
29. A polyacrylonitrile-based carbon fiber, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 28.
Citation Information
Patent Citations
Method for electrochemically modifying surface of ultrasonic-enhanced carbon fiber
CN103321036A
Polyacrylonitrile-based carbon fiber precursor pre-oxidation method
CN111560666A
Ultrahigh-strength medium-modulus polyacrylonitrile-based carbon fiber and preparation method thereof
CN111945251A
Coarse-denier high-strength medium-modulus polyacrylonitrile-based carbon fiber and preparation method thereof
CN112877813A
Cited By
Polyacrylonitrile spinning solution, polyacrylonitrile-based carbon fiber as well as preparation and application of polyacrylonitrile-based carbon fiber
CN121407245A